Answer :
Answer:
(-12,11)
Step-by-step explanation:
x + 2y = 10
3x + 4y = 8
(-2)x + (-2)2y = (-2)10
3x + 4y = 8
-2x - 4y = -20
3x + 4y = 8
Add to eliminate:
x = -12
Substitute x to solve y:
x + 2y = 10
(-12) + 2y = 10
-12 + 2y = 10
2y = 10 + 12
2y = 22
y = 22 ÷ 2
y = 11
Check:
x + 2y = 10
(-12) + 2(11) = 10
-12 + 22 = 10
10 = 10
Answer:
D) (-12, 11)
x = -12
y = 11
Step-by-step explanation:
x + 2y = 10
3x + 4y = 8
Multiply first equation by -3
-3 × (x + 2y) = 10 ➡ -3x - 6y = -30 now add this to second equation
3x + 4y -3x - 6y = 8 - 30 add/subtract like terms (-3x will eliminate 3x)
-2y = -22 divide both sides by 2 since both are negative it will give out a positive result
y = 11 using this we can find the value for x
x + 2y = 10 replace y with the value we found
x + 2×11 = 10
x + 22 = 10
x = -12